Alterações no plano municipal de educação de Passo Fundo : instrumentalização do imaginário social acerca da discussão sobre gênero nas escolas - Silveira, Felipe de Almeida (2021)
The years that followed the protests of June 2013 turned out to be a fertile ground for anti-democratic demonstrations in Brazil. From vicious attacks on the idea of a welfare state and social protection, to unbalanced intrusions between powers (the embryo of operations and controversial judgments such as the Criminal Action 470, the so-called car-wash operation and President Dilma Rousseff's Impeachment Process), we witnessed, absolutely perplexed, the progressive weakening of the idea of social protection and also some sort of criminalization of politics towards some very well-defined targets, applying procedures that clearly violate the guarantees of a Democratic Rule of Law. One of the most disturbing phenomena generated by the political conjuncture was the ‘Nonpartisan School’ movement: aiming to regulate and control the teaching action in public schools arbitrarily interdicting subjects, numerous affiliated projects emerged from the north to the south of Brazil. Here, in the city of Passo Fundo, despite not having an openly identification as such, a similar project was presented to the Legislative House of the city. Initially planned to obliterate the gender debate in municipal schools, city councilors instead of eradicate it, settled for defining the concept in its own terms. What it shown in the foreground hides some subtleties that the political ambiance helps to unveil: the instrumentalization of social imaginary about controversial issues (or matters that are not familiar to public opinion) indicates that the course of the project that changed the goals of the Municipal Plan Education should be closely analyzed. Bronislaw Baczko offers us a very extensive systematization of the dynamics surrounding production and disputes over the social imaginary, bringing up some issues that cross our debate, especially regarding the association between social imaginary and religion. Professor Amy Erica Smith's studies shed a light on the way in which socialization on certain topics relating to morals and sexual and reproductive rights is converted into political support. Brown helps us to understand how the last few decades have contributed to converge with the radicalization of discourses, combining religious fundamentalism and neoliberal economic dynamics, to induce the corrosion of liberal democracy. As we are focusing on the discussion of gender issues, we aimed to demonstrate the way that transgender people and transvesties lives, as they’re the main victims of prejudice and social exclusion, so in order to fulfil this purpose we resorted to a series of researches and data collection. From the literature review, we will build a case study through the analysis of the details of the processing of the aforementioned project, which changed the goals of the Municipal Education Plan of the City of Passo Fundo.